Ovarian reserve in women with endometriosis under total cystectomy compared to partial cystectomy: A randomized clinical trial - Atiye Javaheri; Samane Kabirpour Ashkezar; Maryam Eftekhar; Seiede Zahra Ghanadzade Tafti (Shahid Sadoughi University of Medical Sciences, 2021)
Background: The standard procedure for ovarian endometriosis is laparoscopic excision of ovarian cysts and complete removal of the cyst capsule using the striping technique. Owing to the possibility of reducing ovarian reserve, and in some cases, the premature ovarian failure, the safety remains to be known. Objective: To compare the ovarian reserve in women with endometriosis who underwent total cystectomy with partial cystectomy. Materials and Methods: In this randomized clinical trial, 56 women with endometriosis who were referred to the Research and Clinical Center for Infertility and Shahid Sadoughi Hospital, Yazd, Iran between January and February 2020 were randomly assigned into two groups (n = 25/each); group I (total cystectomy) and group II (partial cystectomy). To assess the ovarian reserves, the anti-Müllerian hormone (AMH) level before and three months after surgery was measured and compared between the two groups. Results: No significant difference was observed in the AMH levels before and after surgery (p = 0.52, p = 0.32, respectively). However, the mean reduction of AMH in total cystectomy group was significantly higher than the partial cystectomy (p = 0.001). Conclusion: Cystectomy in women with endometriosis reduces ovarian reserve and can help maintain some ovarian reserve by performing partial instead of total cystectomy.